Proceedings of the First ACM International Conference on Multimedia - MULTIMEDIA '93 1993
DOI: 10.1145/166266.166282
|View full text |Cite
|
Sign up to set email alerts
|

Open architecture multimedia documents

Abstract: An open architecture multimedia document publication system is described which integrates a number of different representation technologies to provide a medium offering a wide spectrum of usage, from emulation of current paper publication, through electronic document delivery, multimedia inclusion of video and sound, structured hypermedia linkage, and formal knowledge representation supporting simulation and inference. The research is targeted on exploring new forms of scholarly communication, and the publicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…It has been found that information visualization can assist subjects in developing a more robust mental model of the interrelationships to be found in the content (Wenger & Payne, 1994). In addition, several researchers (Gaines & Shaw, 1993; McDonald & Stevenson, 1999) have expressed the belief that users in nonlinear environments need visual aids from their environment in order to alleviate navigational problems, such as the disorientation problem.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that information visualization can assist subjects in developing a more robust mental model of the interrelationships to be found in the content (Wenger & Payne, 1994). In addition, several researchers (Gaines & Shaw, 1993; McDonald & Stevenson, 1999) have expressed the belief that users in nonlinear environments need visual aids from their environment in order to alleviate navigational problems, such as the disorientation problem.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Users can depend on concept maps, and can access multimedia materials through indexing mechanisms. In general, concept maps are used as stand‐alone documents or are embedded as interactive pictures in active documents (Gaines & Shaw, 1993).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Gaines and Shaw [13,14] have developed an active document technology in which a word processor embeds graphics, hypertext link and active components including semantic network functionalities. This has been applied to developing procedure manuals for a corporation, as well as to modeling organizational rules and constraints to be readily understood, updated and used in the organization's information systems.…”
Section: Related Workmentioning
confidence: 99%
“…The HTML specifications of Figure 5 may be embedded within any document, making active semantic networks available as was done with the KWrite knowledgebased word processor Gaines & Shaw, 1993c). Thus, a knowledge structure developed locally can be made available globally together with its linked derivation so that knowledge acquisition and validation can proceed on a distributed basis.…”
Section: Semantic Network Uploaded As Clickable Mapsmentioning
confidence: 99%